Laser-assisted joining of carbon fiber reinforced polyetherketoneketone thermoplastic composite laminates. (December 2022) - Choi, Insung; Doh Roh, Hyung; Nam Jeong, Woo; Young Jeong, Hu; Suh, Jeong; Yi, Jin-Woo; Um, Moon-Kwang; Oh, Youngseok; Lee, Kwang-Hyeon
Graphical abstract: Highlights: Direct joining of 2.2-mm-thick CF-PEKK/CF-PEKK composites via laser-induced heat conduction. Thulium fiber laser emitting at a wavelength of 1940 nm was utilized for this study. Polyetherketoneketone (PEKK) matrix was used for its excellent mechanical properties. Single-lap shear tests for characterization of joining strength were evaluated. Abstract: Carbon-fiber-reinforced thermoplastic (CFRTP) materials have drawn considerable interest owing to their high strength-to-weight ratio. Laser joining technologies have been reported to join CFRTP to metals or plastic materials. However, the direct laser joining of CFRTP/CFRTP is challenging. Herein, we demonstrated the feasibility of laser direct joining of 2.2-mm-thick CFRTP/CFRTP by laser heat conduction. A thulium fiber laser (1940 nm) was used under the optimal joining conditions of 20 W power (beam diameter = 5.5 mm, approximately) and 3 min laser irradiation time. We observed that an increase in the laser irradiation spots per unit area results in a higher joining strength. The joining strengths of carbon fiber (CF)-polyetherketoneketone (PEKK)/CF-PEKK composites were evaluated by single lap shear tests, and the highest average interlaminar shear strength result was 30.9 MPa. Our study indicates that the laser-assisted joining of CF-PEKK/CF-PEKK laminates is viable and worthy of further exploration for industrial applications.